Aspectos reprodutivos da pescada-do-piauí, Plagioscion squamosissimus (Heckel, 1840), capturada no Açude Pereira de Miranda (Pentecoste - Ceará) Reproductive aspects for the pescada-do-piauÌ, Plagioscion squamosissimus (Heckel, 1840), cought in Pereira de (Revista Ciência Agronômica, 2023)
RCA